The profession of sociologist-sociology: The theoretical-practical precepts, the technical practices and the professional procedures of knowledge of the human world - da Silva, Mauro Cesar Rocha; da Silva, Ester Roberto (Seven Editora, 2024)
In the nineteenth century, with the constitution of the capitalist system, social life coexisted with a situation of crisis and social pathologies that put at risk the very sociability of the political system in evidence. At this time, philosophical and naturalist thinkers and intellectuals considered the need for a field of scientific study that would study the causes and origins of social disturbances and problems: sociology emerges – the science of the direction and orientation of society. Its institutionalization process resulted in the professionalization of the sociologist or social scientist and in the school constitution of vast areas of teaching and research. Today, the training of the sociologist is outdated for the resolution of contemporary problems, mainly due to some theoretical-methodological inconsistencies that have not yet been diagnosed or defined with greater precision and methodical systematicity, such as, for example. the theme of subjectivity that has brought all kinds of forms of erratic perceptions and left social science at the mercy of all kinds of antagonism, oppositions and ambiguities of divergent interests and points of view. With the use of the hypothetical-deductive-inductive method of social science and procedures of methods and techniques of investigation, it was identified that social science was constituted on solid bases of scientific foundations that go back to ancient Greek thought, and as Auguste Comte had announced, when he defined the dimension of the social as an objective unit of sociology, conferring to its objectivity the maximum degree, even going so far as to call sociology – the science of the direction and organization of society – as social physics and social mathematics due to its high level of sociological precision of its scientific procedures, in line with the interpretations and explanations of the course of events, facts or phenomena of life in society. DOI:https://doi.org/10.56238/sevened2024.026-017